Optimalisasi Manajemen Keuangan Menggunakan Sistem Excel pada Buku Kas Koperasi Simpan Pinjam Tamara di Desa Tamansari Kecamatan Tegalsari Kabupaten Banyuwangi - Munawir Munawir; Nur Anim Jauhariyah; Cindy Claudia (IAI Darussalam, 2022)
The objectives of this service work program are 1) Maximizing a comprehensive understanding of financial management using the excel system for BUMDes managers; 2) BUMDes managers can use the excel system to make it easier and save time in terms of service and bookkeeping for each transaction. This service is carried out in the savings and loan business unit that manages the TAMARA BUMDes, Tamansari Village, Tegalsari District, Banyuwangi Regency. The approach used is the PAR approach. The results of the service prove that the use of the excel financial system can make it easier for BUMDes managers of savings and loan units so that they can avoid mistakes and make financial transactions easier.